Are You Anxious? A Study of Malaysian University Students during the COVID-19 Pandemic - Yi Jie Ng; Jia Jun Ng; Jie Ying Ng; Xang Ning Ng (AIBPM Publisher, 2023)
Anxiety levels among university students have long been a public health concern. The COVID-19 outbreak, and lockdown have swept the entire world and exacerbated students' stress and anxiety. This study investigates the correlation between independent variables (such as perceived stress, domestic violence, low self-esteem, strained familial relationships, financial constraints, and the presence of chronic diseases) and the dependent variable (anxiety) among university students during the COVID-19 epidemic. The researchers also intend to find out its impacts and provide suggestions on overcoming this issue. A total of 150 students from Universiti Sains Malaysia (USM) participated in the online survey via Google Form. The findings indicate a positive association between perceived stress and low self-esteem with anxiety. Consequently, individuals experiencing anxiety may encounter reduced motivation, lower productivity, suicidal tendencies, or the expression of suicidal thoughts, leading to a deterioration in mental and physical well-being, as well as a negative impact on academic performance. To mitigate these effects, it is recommended that students engage in regular exercise, ensure sufficient sleep, seek professional assistance, strengthen social ties, and adopt stress management techniques. Following these suggestions can help students alleviate stress and enhance their self-esteem.